2010
DOI: 10.1002/syn.20817
|View full text |Cite
|
Sign up to set email alerts
|

Absence of direct effects on the dopamine D2 receptor by mGluR2/3‐selective receptor agonists LY 354,740 and LY 379,268

Abstract: We previously reported the absence of high-affinity binding of the group II metabotropic glutamate receptor agonists LY 354,740 and LY 379,268 to the D2L dopamine receptor. A rebuttal to our findings has since been reported (see Introduction section); this study represents our response. Analysis by LCMS of LY 354,740 and LY 379,268 used in this study revealed the correct molecular mass for these compounds. Both LY 354,740 and LY 379,268 exhibited potent agonist activity for mGluR₂ in the ³⁵S-GTPγS assay. Funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 12 publications
(23 reference statements)
3
13
1
Order By: Relevance
“…This study demonstrated that the PTX-sensitive G i/o subunits, especially G o and G i3 , play important roles in the activation of ERK evoked by amitriptyline. The CellKey TM assay confirmed the pharmacological and siRNA findings, in that the pattern of the change in impedance induced by amitriptyline was similar to that of activation of G i/o -coupled receptors, and not of G s -or G q -coupled receptors (13,14,17,18). Although the C6 cells is an astrocyte model cell line derived from rat glioma, activation of the MMP/FGFR/FRS2␣/ERK cascade occurs in both normal human and rat astrocytes as well (9,11), in a PTX-sensitive manner.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This study demonstrated that the PTX-sensitive G i/o subunits, especially G o and G i3 , play important roles in the activation of ERK evoked by amitriptyline. The CellKey TM assay confirmed the pharmacological and siRNA findings, in that the pattern of the change in impedance induced by amitriptyline was similar to that of activation of G i/o -coupled receptors, and not of G s -or G q -coupled receptors (13,14,17,18). Although the C6 cells is an astrocyte model cell line derived from rat glioma, activation of the MMP/FGFR/FRS2␣/ERK cascade occurs in both normal human and rat astrocytes as well (9,11), in a PTX-sensitive manner.…”
Section: Discussionsupporting
confidence: 65%
“…Electrical Impedance-based Biosensors (CellKey TM Assay)-The CellKey TM assay has been described previously (17,18). Cellular dielectric spectroscopy is a novel technology that employs a label-free, real time, cell-based assay approach for the comprehensive pharmacological evaluation of cells that exogenously or endogenously express GPCRs, and nuclear receptors on the same platform without any modification of the cells.…”
Section: Methodsmentioning
confidence: 99%
“…It could also be argued that the LY379268 doses tested were not high enough to elicit alcohol-like stimulus effects because there were no changes in behavior observed across tested doses. Indeed, the highest dose did not significantly alter response rate (Figure 2b), but acute doses of LY379268 higher than 10 mg/kg produce profound motor impairing effects (Cartmell et al, 2000) and may have nonspecific actions at other receptors (Monn et al, 1999;Seeman and Guan, 2008; but see Fell et al, 2009;Zysk et al, 2011), which would potentially complicate the interpretation of results; therefore, higher doses were not tested in this study.…”
Section: Discussionmentioning
confidence: 95%
“…However, higher doses of LY379268 eroded the improving effect of low dose on spatial tuning, causing the d′ to fall to the level that was not significantly different from the Control condition ( Supplementary Figure 4b; P40.9), thus compromising the specificity of working memory representations. The nonspecific actions of LY379268 at high doses may arise from its off-target interactions with the dopamine system, 55 but this issue remains controversial 56,57 and there may be other possibilities underlying the mixed effect at high doses. mGluR2/3 antagonist reverses APDC beneficial actions.…”
Section: Subcellular Localization Of Mglur2/3 In Primate Dlpfcmentioning
confidence: 99%